Two S = 1/2 one-dimensional barium copper phosphates showing antiferromagnetic and ferromagnetic intrachain interactions. Issue 8 (20th January 2016) - Yang, Ming; Cui, Meiyan; Zhang, Suyun; Xiang, Hongping; Guo, Wenbin; He, Zhangzhen
Abstract : Compound1 contains alternating chains with 3D ordering at 14 K, while2 consists of uniform chains without 3D ordering above 2 K. Abstract : Two barium copper phosphates, BaCu2 (PO4 )2 (H2 O) (1 ) and Ba2 Cu(HPO4 )(PO4 )(OH) (2 ), were synthesized under mild hydrothermal conditions. The Cu cation in1 adopts a CuO4 (H2 O) square pyramidal coordination configuration, forming alternating chains along the b axis through alternative corner and edge sharing, while the geometry of the Cu center in2 is a CuO4 (OH)2 octahedron which further connects each other by edge sharing to constitute uniform chains along the b axis. Magnetic behaviors of both compounds were analyzed by susceptibility, magnetization and heat capacity measurements. The dominant intrachain couplings are antiferromagnetic in1 with a long-range ordering at 14 K and ferromagnetic in2 without long-range ordering above 2 K. The first principles calculations indicate that the intrachain ferromagnetic couplings in2 originate from Cu(1)–O(7)H–Cu(1) d pσ correlation superexchanges. The susceptibility data of compounds1 and2 are fitted by using suitable antiferromagnetic chain and ferromagnetic chain models, respectively. In addition, we report the results of the infrared and thermal measurements of both the compounds.